Using the OK Modes Model to Enhance Clarity in Communication. (January 2017) - Mountain, Anita
The author believes that there is a need to update transactional analysis (TA) theory so that it is congruent and applicable today, particularly in relation to the concepts of structural and functional ego states. Earlier references to the Adult ego state as a data processor led to a mix-up within transactional analysis between using Parent and Child to indicate the past when referring to structural ego states and then, conversely, to the present in the functional ego states model. This article addresses this confusion and outlines the rationale for a more recent model designed to replace the functional model and to outline transactions based on OKness. Titled OK Modes (Mountain & Davidson, 2011), this model is appropriate for all fields of transactional analysis, although this article focuses on its use in the organizational field. The author's aim is to develop a theoretically rational model that is congruent with the structural model of ego states.